2021
DOI: 10.1111/evj.13402
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the neuroanatomy of the equine thoracolumbar vertebral column with regional anaesthesia and complications following desmotomy of the interspinous ligament

Abstract: Impinging/overriding dorsal spinous processes (DSPs) of the thoracolumbar vertebrae are a common cause of poor performance in horses. In the last five decades, numerous surgical treatments have been reported on, from transverse transection of the affected DSPs, and endoscopic resection of the affected DSPs, to transection of the interspinous ligament. Until recently, cosmetic outcomes have been reported as good to excellent in studies. However, a previously unreported complication of neurogenic atrophy of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Epidural spread was found in 20% of the horses (unilateral epidural spread occurred in one of the two injections for each horse). Epidural spread following ESP injections is inconsistent and difficult to predict and has been considered as one of the factors contributing towards clinical analgesia after performing the ESP block in both human and dogs 7,67–69 . However, due to the inconsistent and unpredictable epidural spread, one must consider that the final contribution towards analgesia will be uncertain for each patient.…”
Section: Discussionmentioning
confidence: 99%
“…Epidural spread was found in 20% of the horses (unilateral epidural spread occurred in one of the two injections for each horse). Epidural spread following ESP injections is inconsistent and difficult to predict and has been considered as one of the factors contributing towards clinical analgesia after performing the ESP block in both human and dogs 7,67–69 . However, due to the inconsistent and unpredictable epidural spread, one must consider that the final contribution towards analgesia will be uncertain for each patient.…”
Section: Discussionmentioning
confidence: 99%
“…The reported mechanism of action of the ISLD is to remove tension on afferent nociceptive receptors located at the level of the insertion in the interspinous ligament insertion to reduce pain by transection of the interspinous ligament, which can cause a mild enlargement in the space between impinging DSPs 2,7 . However, if extensive bone bridging has formed between the DSPs, then ISLD may be unsuccessful, and by positioning the Mayo scissors in a more obtuse angulation to facilitate transection, this can cause iatrogenic damage to the neighboring nerves 8,14 . This may lead to neurogenic atrophy of a small portion of the epaxial musculature and an associated cosmetic abnormality 8,14 .…”
Section: Discussionmentioning
confidence: 99%
“…2,7 However, if extensive bone bridging has formed between the DSPs, then ISLD may be unsuccessful, and by positioning the Mayo scissors in a more obtuse angulation to facilitate transection, this can cause iatrogenic damage to the neighboring nerves. 8,14 This may lead to neurogenic atrophy of a small portion of the epaxial musculature and an associated cosmetic abnormality. 8,14 In addition, by not removing the impinging and abnormal bone, recurrence of clinical signs could occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ISL occupies the space between the DSPs and interspinous ligament desmotomy (ISLD) has been shown to ameliorate back pain (Coomer et al, 2012) but its effects on increasing mobility of the spine are unknown. Several studies have shown a clinical improvement in horses suffering from poor performance post-ISLD (Prisk and García-López, 2019;Brown et al, 2020), however, others have mentioned long-term complications such as unilateral neurogenic atrophy of epaxial musculature (Derham et al, 2021). The main effects of ISLD appear to be due to reduced tension on the afferent nociceptive receptors located at the ligament insertion, which abolish the pain response (Coomer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%